Analysis on the practical application of Chinese national elements into the international standard dance repertoir - Xie Changlong (ХДАК, 2025)
In the context of globalization, cultural exchanges are increasingly frequent, and Chinese national elements are more and more widely used on the international stage. As an art form across national boundaries, international standard dance integrates Chinese national elements, which not only enriches the expressive force of dance, but also promotes the dissemination and exchange of culture. It has great cultural and social significance to study the practical application of Chinese ethnic elements in international standard dance repertoire.
qualification work for obtaining master’s degree in specialty 024 Choreography
Keywords: хореографічне мистецтво Китаю; танці народні китайські